PENGARUH DESAIN PRODUK DAN PROMOSI TERHADAP VOLUME PENJUALAN PADA INDUSTRI BATIK (Studi Pada Industri Batik di Kabupaten Sragen ) - Padmantyo, Sri; Purnomo, Eko (Benefit, 2013)
This study was aimed at analyzing the effect of product design and promotion on salesÂ volume in the batik industry in Sragen. This study is expected to provide a material considerationÂ in the determination of product design and promotion policies that can improve the companyâsÂ sales volume. This study took 50 companies in Sragen batik as the study sample. This study testedthree hypotheses. The first hypothesis says that the design of the products significantly influenceÂ sales volume, is supported. This study also supports the second hypothesis which says that theÂ promotion of a significant effect on sales volume. The third hypothesis is that the design of theÂ product and promotion are jointly significant effect on the volume of sales is also supported.